Direct Visualization of Microtubule Flux during Metaphase and Anaphase in Crane-Fly Spermatocytes - LaFountain, James R. (The American Society for Cell Biology, 2004)
Microtubule flux in spindles of insect spermatocytes, long-used models for studies on chromosome behavior during meiosis, was revealed after iontophoretic microinjection of rhodamine-conjugated (rh)-tubulin and fluorescent speckle microscopy. In time-lapse movies of crane-fly spermtocytes, fluorescent speckles generated when rh-tubulin incorporated at microtubule plus ends moved poleward through each half-spindle and then were lost from microtubule minus ends at the spindle poles. The average poleward velocity of ∼0.7 μm/min for speckles within kinetochore microtubules at metaphase increased during anaphase to ∼0.9 μm/min. Segregating half-bivalents had an average poleward velocity of ∼0.5 μm/min, about half that of speckles within shortening kinetochore fibers. When injected during anaphase, rhtubulin was incorporated at kinetochores, and kinetochore fiber fluorescence spread poleward as anaphase progressed. The results show that tubulin subunits are added to the plus end of kinetochore microtubules and are removed from their minus ends at the poles, all while attached chromosomes move poleward during anaphase A. The results cannot be explained by a Pac-man model, in which 1) kinetochore-based, minus end-directed motors generate poleward forces for anaphase A and 2) kinetochore microtubules shorten at their plus ends. Rather, in these cells, kinetochore fiber shortening during anaphase A occurs exclusively at the minus ends of kinetochore microtubules.